1985
DOI: 10.1103/physrevlett.54.701
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Aggregates in Sputter-Deposited NbGe2Films

Abstract: Fractal-like structures have been observed in sputter-deposited thin films of NbGe2. These structures exhibit a striking resemblance to those produced by computer simulations of diffusionlimited aggregation using the Witten-Sander model. An effective fractal dimensionality of about 1.9 has been determined from digitized photomicrographs. Our results indicate a two-stage growth process in which an initial structure with a fractal dimensionality of about 1.7 is thickened by a subsequent growth process.PACS numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(15 citation statements)
references
References 6 publications
0
14
1
Order By: Relevance
“…This model neither correlates the fractal patterns with the microstructure in detail nor systematically considers the dependence of the fat fractal patterns on the annealing temperature and time or the film thickness ratio, and nor systematically considers the dependence of fractal growth on the nanocrystals formation. In previous studies [55,148,238,244,246,[267][268][269][270][271][272][273][274][275][276][277][278][279][280][281][282][283], we found that the mechanism of the fractal formation in metal/semiconductor bilayer films is completely different from DLA mechanism. Fox example, Hou and Wu [244,273] suggested that the appearance of fractal-like patterns in Si-ion-implanted amorphous Ge/ Au (abbreviated as a-Ge/Au) bilayer films after annealing was due to the Random-Successive Nucleation (RSN) of polycrystalline Ge grains, while they deposited Au at first and then Ge without breaking the vacuum, and the thickness of polycrystalline Au and amorphous Ge films was about 25 and 30 nm, respectively, (the total thickness of the bilayer films was about 55 nm).…”
Section: Microstructural Evaluation Of Metal/semiconductor Thin Filmsmentioning
confidence: 50%
See 3 more Smart Citations
“…This model neither correlates the fractal patterns with the microstructure in detail nor systematically considers the dependence of the fat fractal patterns on the annealing temperature and time or the film thickness ratio, and nor systematically considers the dependence of fractal growth on the nanocrystals formation. In previous studies [55,148,238,244,246,[267][268][269][270][271][272][273][274][275][276][277][278][279][280][281][282][283], we found that the mechanism of the fractal formation in metal/semiconductor bilayer films is completely different from DLA mechanism. Fox example, Hou and Wu [244,273] suggested that the appearance of fractal-like patterns in Si-ion-implanted amorphous Ge/ Au (abbreviated as a-Ge/Au) bilayer films after annealing was due to the Random-Successive Nucleation (RSN) of polycrystalline Ge grains, while they deposited Au at first and then Ge without breaking the vacuum, and the thickness of polycrystalline Au and amorphous Ge films was about 25 and 30 nm, respectively, (the total thickness of the bilayer films was about 55 nm).…”
Section: Microstructural Evaluation Of Metal/semiconductor Thin Filmsmentioning
confidence: 50%
“…Moreover, the sample annealed at 70 min with the lower fractal dimension value has higher number of fine branches and larger fractal size. Such behavior is not completely consistent with the theories based on diffusion-limited aggregation and previous experimental observations [245,[267][268][269]. In DLA model, Witten et al found that the DLA is an idealization of the process by which matter irreversibly combines to form dust, soot, dendrites, and other random objects in the case where the rate-limiting step is diffusion of matter to the aggregate.…”
Section: Interdiffusion Assessment Of Au/ge Bilayer Filmsmentioning
confidence: 65%
See 2 more Smart Citations
“…Sputtering is a simple and useful technique for preparing thin films with expected structure and properties, and recently, the growth of some interesting fractal aggregates on solid surface were also studied by this process [16,17]. In the present work, a-C films were prepared by magnetron sputtering on substrates as Si (1 0 0) and glass, without any special pretreatment.…”
Section: Introductionmentioning
confidence: 99%